THE APPLICATION OF ARTIFICIAL INTELLIGENCE FOR DESIGNING BATIK MOTIF - Eka Legya Frannita; Anwar Hidayat; Wawan Budi Setyawan (Berkala Penelitian Teknologi Kulit, Sepatu, dan Produk Kulit, 2024)
Artificial intelligence was a popular technology that was successfully utilized in several fields including of fashion industry. Recently, several research communities have been done in employing artificial intelligence for increasing the productivity. This research work aims to create batik pattern using artificial intelligence which was conducted in three major processes. The three processes were brainstorming process, designing process, and validation. Brainstorming process aimed to determine the restriction of this research work. Designing process focused on the utilization of artificial intelligence for creating batik pattern. In this process, we used online illustration maker based artificial intelligence. Validation process aimed to evaluate the originality of result. According to evaluation process using Google Lens, it can be concluded that the resulted design was original in which there is another batik patterns that similar to our result.